2022
DOI: 10.3390/jcm11082238
|View full text |Cite
|
Sign up to set email alerts
|

Positivity Trends of Bacterial Cultures from Cases of Acute and Chronic Periprosthetic Joint Infections

Abstract: Background: There is no clear distinction in the literature regarding the positivity trends of bacterial cultures in acute and chronic prosthetic joint infections. Methods: We prospectively included in this study all consecutive patients, aged over 18 years, that were hospitalized from September 2016 through December 2019, that underwent a joint arthroplasty revision surgery. Results: Forty patients were included in our analysis, 11 acute/acute hematogenous and 29 chronic PJIs. We were able to identify all str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…We were able to group the 67 patients diagnosed with a periprosthetic joint infection, using the classification proposed by Zimmerli et al, as follows: ten patients were diagnosed with early PJI, nine patients with delayed PJI, and forty-eight patients were diagnosed with a late PJI. Again, using the classification of the periprosthetic joint infections proposed in the Pocket Guide by the PRO-IMPLANT Foundation as we did in previously published articles [ 22 ], eight patients were diagnosed with an acute perioperative infection, four patients with acute hematogenous infection, and fifty-five patients with chronic PJI. We will report all our results using this classification.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We were able to group the 67 patients diagnosed with a periprosthetic joint infection, using the classification proposed by Zimmerli et al, as follows: ten patients were diagnosed with early PJI, nine patients with delayed PJI, and forty-eight patients were diagnosed with a late PJI. Again, using the classification of the periprosthetic joint infections proposed in the Pocket Guide by the PRO-IMPLANT Foundation as we did in previously published articles [ 22 ], eight patients were diagnosed with an acute perioperative infection, four patients with acute hematogenous infection, and fifty-five patients with chronic PJI. We will report all our results using this classification.…”
Section: Resultsmentioning
confidence: 99%
“…Prosthetic joint infections occur at a frequency of 1 to 3% and are still a major cause of healthcare expenditure [ 20 ]. Other authors report that periprosthetic joint infections of the hip and knee occur in approximately 1 to 2% of patients after total joint arthroplasties [ 21 , 22 ]. These are complications that lead to a prolonged hospital stay, multiple surgeries, and functional impairment [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, some studies have shown that surgery can also induce immunosuppression. For example, phagocytic activity in specific cells (PMN, monocytes, and macrophages) is reduced during the postoperative period, which makes patients more susceptible to infection [172][173][174][175][176][177][178][179][180][181][182][183][184].…”
Section: Orthopedic Surgeries and Inflammatory Signaturesmentioning
confidence: 99%